Analisis Kinerja Manajerial Pada Bank Konvensional di Kota Lubuklinggau - Effendi, Muhammad; Fitria, Fitria; Syahrani, Tiara (Jurnal Ilmu Manajemen, 2022)
This research aims to find out how much influence the accounting control system, performance measurement system, reward system and decentralization on managerial performance on conventional banks in Lubuklinggau City. This research was conducted at all conventional banks in Lubuklinggau City. The population and sample in this study were managers or heads of conventional bank sections in Lubuklinggau City. The data used is primary data obtained from the results of the spread of questionnaires to managers or heads of conventional bank sections in Lubuklinggau City. The method used is multiple regression analysis. The data analysis technique used is quantitative descriptive with the help of THE SPSS program. From the test showed that the first hypothesis that the accounting control system affects manjerial performance is evidenced by a sig value of 0.046<0.005. Testing the second hypothesis showed that the performance measurement system had an effect on managerial performance, as evidenced by a sig value of 0.004<0.05. Testing the third hypothesis showed that the reward system had an effect on managerial performance, as evidenced by a sig value of 0.011<0.05. Testing the fourth hypothesis showed that the decentralized system of performance had an effect on managerial performance, as evidenced by a sig value of 0.002<0.05.